El modelo actual de desarrollo turístico al oeste del balneario La Paloma, Rocha, Uruguay. Tendencias, riesgos y propuestas - Gadino, Isabel; Brazeiro, Alejandro; Panario, Daniel; Roche, Ingrid; Gutiérrez, Ofélia (Sustainability in Debate, 2013)
This article analyzes the development model of the Atlantic coast of Uruguay and its capacity to preserve relevant ecosystem services. The chosen study area was Playa Solari ”“ Barra, one of the most important touristic spots of Uruguay (located in Laguna de Rocha, Rocha, Uruguay). This coastal zone has experienced important territorial changes during the last decades, with conflicts arising among traditional urban development for beaches, the recent strategies of rural-coastal tourism and natural and cultural heritage conservation strategies. The results show that the strong process of urban consolidation is negatively affecting the most important economic resources and ecosystem services in the study area, particularly those that directly promote touristic activities. For the last five years, the trend of urban development seems to point out towards an increase of the observed negative effects. Based on that evidence, this paper proposes specific strategies, particularly a new land use model, to revert negative impacts.